Answer:
16
Step-by-step explanation:
Answer:
Y'=3xy-3x-12
Y'=F(-2,-1)=0
Step-by-step explanation:
The function of the equation at the point (-2,-1)
is where the equation make the function go to zero:
Y'=3xy-3x-12
Y'=F(-2,-1)=[3(-2)(-1)]-[3(-1)]-12
F(-2,-1)=[6]-[-6]-12
F(-2,-1)=6+6-12
F(-2,-1)=12-12
F(-2,-1)=0
Solving for y
3xy-3x-12=0
y=4/x+x
Making y=0
![\frac{4}{x}+x=0](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bx%7D%2Bx%3D0)
![x^{2} =-4](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%3D-4)
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
So the values make the function go to zero
Nothing else is given, so for the two triangles to be congruent, the only possible proof is the ASA theorem.
first pairs of angles: 2x+7=x+21 => x=14
second pairs of angles: 8y-4=4y+28 =>y=8
The two triangles share the same side PR
Based on the Angle-Side-Angle Triangle Congruence theorem, these two triangles are congruent with x=14, y=8
(2x+7) +(8y-4) +Q=180 =>85
Answer:
9 1/3
Step-by-step explanation:
Make 2/3 , 1/2 , & 1/6 have the same denominator. 6 is the least common multiple for all 3 fractions.
2/3 gets multiplied by 2/2
1/2 gets multiplied by 3/3
1/6 stays the same
2/3 becomes 4/6
1/2 becomes 3/6
1/6 stays 1/6
Follow the order of operations from the original equation.
4/6 - 3/6 = 1/6 then 1/6 + 1/6 = 2/6
6 - 1 = 5 then 5 + 4 = 9
Simplify 2/6 to 1/3
Remember to add 1/3 back to 9 making it 9 1/3
Answer:
.06 or six hundredths
Step-by-step explanation: